THE PILLARS OF EDUCATION AND OLYMPIC VALUES IN CLASSES OF PHYSICAL EDUCATION AS A MEAN OF INTEGRAL DEVELOPMENT STUDENTS (Fiep Bulletin - online, 2013)
The sport can be considered a means to develop skills and abilities necessary for human development. It can be understood as a social phenomenon to play an important role in the formation of man and of society. The Pillars of the sport coupled with education and Olympic values??, developed in school physical education classes, aims to contribute to human development and the promotion of peace. The aim of this study was to investigate how the Olympic values ??and the pillars of education can be worked into the physical education classes in order to contribute to the process of human development of students. The literature review was the method used in order to highlight the relationship between sport, education and the Olympic values??. Finally, it is of fundamental importance that physical education classes are organized based on the Olympic Education, so that cognitive skills, relational, personal and productive are developed and therefore students can use them in their life every day.
Keywords: Sport; Olympic Values; Pillars of education.